Formative Assessment and Science Education - Bell, Nigel. author. aut Link
VIII, 148 p.
Keywords: Formative Assessment and Science Education documents the findings of a research project which investigated the ways in which teachers and students used formative assessment to improve the teaching and learning of science in some New Zealand classrooms. The research documented in this book used the definition of formative assessment as `the process used by teachers and students to recognise and respond to students' learning, in order to enhance that learning, during the learning'. The book contains one detailed case study from the research, as well as cameos of instances of formative assessment. The book also contains two summaries of the research findings - a model developed to describe the process of formative assessment used by the teachers and students involved in the research, and a summary of the characteristics of formative assessment. The findings are also theorised with respect to sociocultural and discursive views of learning. This research will be of interest to graduate students and researchers, as well as teacher educators, curriculum developers, and assessment specialists.